Benign liver tumors in pediatric patients - Review with emphasis on imaging features - Chiorean, Liliana; Cui, Xin-Wu; Tannapfel, Andrea; Franke, Doris; Stenzel, Martin; Kosiak, Wojciech; Schreiber-Dietrich, Dagmar; Juengert, Joerg; Chang, Jian-Min; Dietrich, Christoph F. (World Journal of Gastroenterology, 2015)
Benign hepatic tumors are commonly observed in adults, but rarely reported in children. The reasons for this remain speculative and the exact data concerning the incidence of these lesions are lacking. Benign hepatic tumors represent a diverse group of epithelial and mesenchymal tumors. In pediatric patients, most benign focal liver lesions are inborn and may grow like the rest of the body. Knowledge of pediatric liver diseases and their imaging appearances is essential in order to make an appropriate differential diagnosis. Selection of the appropriate imaging test is challenging, since it depends on a number of age-related factors. This paper will discuss the most frequently encountered benign liver tumors in children (infantile hepatic hemangioendothelioma, mesenchymal hamartoma, focal nodular hyperplasia, nodular regenerative hyperplasia, and hepatocellular adenoma), as well as a comparison to the current knowledge regarding such tumors in adult patients. The current emphasis is on imaging features, which are helpful not only for the initial diagnosis, but also for pre- and post-treatment evaluation and follow-up. In addition, future perspectives of contrast-enhanced ultrasound (CEUS) in pediatric patients are highlighted, with descriptions of enhancement patterns for each lesion being discussed. The role of advanced imaging tests such as CEUS and magnetic resonance imaging, which allow for non-invasive assessment of liver tumors, is of utmost importance in pediatric patients, especially when repeated imaging tests are needed and radiation exposure should be avoided.
EVALuna2:18922